Relationships of Cardiorespiratory Fitness with Metabolic Risk Factors, Inflammation, and Liver Transaminases in Overweight Youths - Dominique Bouglé; Gautier Zunquin; Bruno Sesbouë; Jean-Pierre Sabatier (Hindawi Limited, 2010)
The aim of this study was to assess the relationships of fatness and fitness with metabolic risk factors, including liver transaminases and inflammation in obese youth, taking in account gender, age, and pubertal stage. 241 children were studied (135 girls), age 11.9±2.2 years (x±SD), Body Mass Index z score 5.4±2.7. For girls, VO2max was significantly associated with insulin (P=.001), Insulin resistance (HOMA-IR) (P=.005), and ALT (P=.012); a relationship was displayed between fibrinogen and age and % fat mass (FM) (P=.008); for boys, relationships were found between VO2max and diastolic blood pressure and triglycerides; independent associations were also found between age and insulin, HOMA-IR and HDL cholesterol; fibrinogen and sedimentation rate were related (P≤.004) with %FM. Their relationships are observed from young age and increase with the continuous increase of factors. This supports the need to treat overweight as soon as it is detected; improving CRF is one of the ways which could be used to prevent the complications of obesity.